2021
DOI: 10.3390/ijms22073385
|View full text |Cite
|
Sign up to set email alerts
|

Evodiamine Inhibits Helicobacter pylori Growth and Helicobacter pylori-Induced Inflammation

Abstract: Helicobacter pylori (H. pylori) classified as a class I carcinogen by the World Health Organization (WHO) plays an important role in the progression of chronic gastritis and the development of gastric cancer. A major bioactive component of Evodia rutaecarpa, evodiamine, has been known for its anti-bacterial effect and anti-cancer effects. However, the inhibitory effect of evodiamine against H. pylori is not yet known and the inhibitory mechanisms of evodiamine against gastric cancer cells are yet to be elucida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 68 publications
0
19
0
1
Order By: Relevance
“…Gastric epithelial cell line, AGS (Zhu et al, 2017;Yang et al, 2021), was obtained from the American Type Culture Collection (Manassas, VA, United States) and BGC-823 (Tang et al, 2013;Guo et al, 2020) was obtained from the Shanghai Institute CellBank, Chinese Academy of Sciences. The two cell lines were thawed and cultured in 3 ml of the complete Ham's F12 medium (1 × 10 5 cells/well) in a 12-well plate.…”
Section: Cell Linesmentioning
confidence: 99%
“…Gastric epithelial cell line, AGS (Zhu et al, 2017;Yang et al, 2021), was obtained from the American Type Culture Collection (Manassas, VA, United States) and BGC-823 (Tang et al, 2013;Guo et al, 2020) was obtained from the Shanghai Institute CellBank, Chinese Academy of Sciences. The two cell lines were thawed and cultured in 3 ml of the complete Ham's F12 medium (1 × 10 5 cells/well) in a 12-well plate.…”
Section: Cell Linesmentioning
confidence: 99%
“…Studies have shown that the incidence of gastric cancer in whites is twice that of other races [29] . Long-term follow-up of the disasters in Hiroshima and Nagasaki Studies have shown that radiation has been identified as a high-risk risk factor for gastric cancer [30] . Early diagnosis of gastric cancer is still difficult worldwide and it is difficult to make a correct diagnosis under endoscopy in the early stage [14,31] .…”
Section: Resultsmentioning
confidence: 99%
“…However, this mechanism needs to be further proved. In addition, studies have shown that VacA can also regulate mitogen-activated protein kinase pathway, phosphorylation of protein kinase B pathway, and autophagy, which also had relationship with inflammation and cell apoptosis [ 31–33 ]. Therefore, whether VacA can regulate other signaling pathways in lung injury remains to be further investigated.…”
Section: Discussionmentioning
confidence: 99%